2011
DOI: 10.1002/anie.201000873
|View full text |Cite
|
Sign up to set email alerts
|

2‐Iodoxybenzoic Acid—A Simple Oxidant with a Dazzling Array of Potential Applications

Abstract: Since its discovery by Christoph Hartmann and Victor Meyer in 1893, 2-iodoxybenzoic acid (IBX) has emerged as a rather ubiquitous oxidant for organic synthesis. The past decade has seen the development of a large variety of applications that go far beyond the simple oxidation of alcohols. This Review is concerned with the synthetic potential of IBX, with particular emphasis on uncommon reactivity patterns and novel fields of application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(75 citation statements)
references
References 585 publications
(246 reference statements)
2
71
0
2
Order By: Relevance
“…16,17) Nowadays, the environmentally-benign hypervalent iodine oxidation has witnessed significant progress in the field of organic chemistry. [18][19][20][21][22][23][24][25][26][27][28][29][30] We have been engaged in the development of the oxidation of the sulfur atom utilizing hypervalent iodine reagents to form an active iodonium intermediate. 31,32) Thus, we have recently developed novel methods of hypervalent iodine-induced glycosylation of thioglycoside.…”
mentioning
confidence: 99%
“…16,17) Nowadays, the environmentally-benign hypervalent iodine oxidation has witnessed significant progress in the field of organic chemistry. [18][19][20][21][22][23][24][25][26][27][28][29][30] We have been engaged in the development of the oxidation of the sulfur atom utilizing hypervalent iodine reagents to form an active iodonium intermediate. 31,32) Thus, we have recently developed novel methods of hypervalent iodine-induced glycosylation of thioglycoside.…”
mentioning
confidence: 99%
“…The obtained solid was washed with Et 2 O three times and dried in a vacuum to provide dibenziodolium trifluoromethanesulfonate 10 (0.781 g, 91% yield) as a white solid; mp 247−249°C. 1 Preparation of Dibenziodolium Bis(trifluoromethane)sulfonimide (11). To a stirred solution of 2-iodobiphenyl (0.56 g, 0.35 mL, 2.0 mmol) in anhydrous CH 2 Cl 2 (6.0 mL) were added m-CPBA (77%, 0.736 g, 3.2 mmol) and a solution of HNTf 2 (1.26 g, 4.5 mmol) in CH 2 Cl 2 (5.0 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Such requirements are often met in the hypervalent iodine reagents, 3 whose chemistry has experienced remarkable growth during the last decades mainly in oxidation processes. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] In the light of these properties of organoiodine reagents, Zhang et al, 18 reported recently a method of broad scope for the coupling of carboxylic acids with amines or alcohols, using the hypervalent iodine lactone 1 as coupling reagent (Scheme 1). Treatment of carboxylic acids with amines or alcohols in the presence of lactone 1, triphenylphosphine and dimethylaminopyridine (DMAP), gave respective amides or esters in high yields.…”
Section: Introductionmentioning
confidence: 99%